2023
DOI: 10.20473/jmtt.v16i1.43224
|View full text |Cite
|
Sign up to set email alerts
|

How Do Servant Leadership and Knowledge Sharing Trigger Innovative Work Behaviors among Millennials at Start-up Businesses?

Abstract: Purpose:Technological developments and environmental changes are currently growing rapidly. This adaptation indirectly requires a company to continue to innovate, especially in the development of Start Up software. This study aims to examine the relationship between servant leadership and knowledge sharing on innovative work behavior. This study also explores the mediating role of creative self-efficacy on innovative work behavior. Design/methodology/approach: Data was collected from 120 millennial Start Up em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Furthermore, perceived servant leadership significantly and positively impacts innovative self-efficacy among these students, corroborating the findings of Dayanti and Yulianti (2023), Zainal and Lata (2021), Iqbal et al (2022), and Suhartanti and Prasetyanto (2022). Through positive emotional support and encouragement, servant leadership conveys to students that they are recognized, trusted, and capable of facing new challenges (Khan et al, 2022).…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, perceived servant leadership significantly and positively impacts innovative self-efficacy among these students, corroborating the findings of Dayanti and Yulianti (2023), Zainal and Lata (2021), Iqbal et al (2022), and Suhartanti and Prasetyanto (2022). Through positive emotional support and encouragement, servant leadership conveys to students that they are recognized, trusted, and capable of facing new challenges (Khan et al, 2022).…”
Section: Discussionsupporting
confidence: 74%
“…Some examples of research of this topic in service industry are: in high-tech company (Su et al, 2020), school institutions (Anshori et al, 2023;Hermanto & Srimulyani, 2022), hotel (Ling et al, 2016), college teachers (Shailja et al, 2023), and public company (Chen et al, 2022). These studies have found that servant leadership enhance job engagement (Kaya & Karatepe, 2020), innovative work behavior (Dayanti & Yulianti, 2023;Shailja et al, 2023;Su et al, 2020;Yoshida et al, 2014), creative process engagement (Chen et al, 2022), higher performance (Hermanto & Srimulyani, 2022), organizational citizenship behavior and extra role behavior (Hermanto & Srimulyani, 2022), and career satisfaction (Kaya & Karatepe, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In general, servant leadership behavior encourages the emergence of several positive outcomes (Cai et al, 2018;Hermanto & Srimulyani, 2022;Ling et al, 2016;Su et al, 2020). Some of them are employees' ability and desire to work innovatively (Cai et al, 2018;Dayanti & Yulianti, 2023;Yoshida et al, 2014), follower performance and motivation (Anshori et al, 2023), employees' service quality (Ling et al, 2016), and lower level of employees' deviance behavior (Sendjaya et al, 2019), meaning that the core essence of the servant leadership model lies in its emphasis on behaviors that prioritize the contributions of followers and support their ability to reach their full potential.…”
Section: Introductionmentioning
confidence: 99%